Bovine Immunoglobulin E Levels of Bali Cattlesin Bangli and Nusa Penida island Bali Province, Indonesia - Ni Ketut Suwiti; Luh Gde Surya Heryani; Desak Nyoman Dewi Indira Laksmi; Ni Nyoman Werdi Susari; I Nengah Kerta Besung (Journal of Veterinary and Animal Sciences, 2019)
The aim of this research was to detect identify levels of Bovine Immunoglobulin E (BoIg.E), can be used as an indicator of response immune in bali cattle. Eighty serum samples were collected from Nusa Penida and Bangli region. Bovine Ig.E levels was measured using a commercial Enzyme Linked Immunosorbent Assay (ELISA) Kit. The data were analysis based on differences of farming characteristics andgeographic. The result of research that, of BoIg.E level of bali cattle kept in Bangli (34.16258 ?g/ml), was higher than Nusa Penida (22.26047 ?g/ml). We conclude that there was a significant effect of differences of farming characteristics and geographic conditions.